Profile in various organic soil depth shrimp pond, Tambak Inti Rakyat, Karawang - Hastuti, Yuni Puji; Novita, Lena; Widiyanto, Tri; Rusmana, Iman (Jurnal Akuakultur Indonesia, 2011)
ABSTRACTOrganic material in the bottom of the pond is part of the land is a complex and dynamic system, which is sourced from the rest of the feed, plants, and or animals found in the soil that continuously change shape, because it is influenced by biology, physics, and chemistry. This study was aimed to see the profile of organic material consisting of C, N, and C/N ratio and phosphate in different depths of pond with different culture systems. Observation were conducted at Tambak Inti Rakyat, Karawang in traditional, semi-intensive and intensive culture systems. Observation at mangrove area was also observed as control. Sediment samples at the inlet and outlet at three different depths (0‒5 cm, 5‒10 cm, and 10‒15 cm) was taken every 30 days to measure the content of C, N, C/N ratio, and total phosphate. During the 120 day maintenance period could be known that in all pond systems were used (traditional, semi-intensive, and intensive) the concentration of C-organic and organic-N on average was located in the bottom layer which is a layer of 10‒15 cm. The lack of human intervention from ground pond system, the more diverse the type and amount of organic material contained therein.Keywords: organic materials, subgrade, depth, aquaculture systems, long maintenanceABSTRAKBahan organik di dasar tambak merupakan bagian dari tanah yang merupakan suatu sistem kompleks dan dinamis, yang bersumber dari sisa pakan, tanaman, dan atau binatang yang terdapat di dalam tanah yang terus menerus mengalami perubahan bentuk, karena dipengaruhi oleh faktor biologi, fisika, dan kimia. Penelitian ini bertujuan untuk melihat profil bahan organik yang terdiri dari C, N, dan C/N rasio serta fosfat pada kedalaman tambak yang berbeda dengan sistem budidaya yang berbeda pula. Pengamatan dilakukan di Tambak Inti Rakyat Karawang pada sistem budidaya tradisional, semi intensif, dan intensif. Pengamatan di daerah mangrove diamati pula sebagai kontrol. Sampel sedimen di inlet dan outlet pada tiga kedalaman yang berbeda (0‒5 cm, 5‒10 cm, dan 10‒15 cm) diambil setiap 30 hari sekali untuk diukur kandungan C, N, C/N rasio, dan total fosfatnya. Selama 120 hari masa pemeliharaan dapat diketahui bahwa pada semua sistem tambak yang digunakan (tradisional, semi intensif, dan intensif) nilai konsentrasi C-organik dan N-organik rata-rata terletak pada lapisan paling bawah yaitu lapisan 10‒15 cm. Minimnya campur tangan manusia dari tanah sistem tambak maka semakin beragam jenis dan jumlah dari bahan organik yang terkandung di dalamnya.Kata kunci: bahan organik, tanah dasar, kedalaman, sistem budidaya, lama pemeliharaan